Genomic architecture of phenotypic divergence between two hybridizing plant species along an elevational gradient. (18th August 2015) - Brennan, Adrian C.; Hiscock, Simon J.; Abbott, Richard J.
Abstract : Hybrid zones that occur across environmental gradients provide excellent opportunities for studying the maintenance of divergent adaptations in the presence of gene flow. They also provide insight into the biodiversity implications of future species contact and hybridization in a changing world. We studied divergent morphology between two Senecio (ragwort) species that form a natural hybrid zone with respect to elevation on Mount Etna, Italy, using a quantitative trait locus (QTL) mapping approach. We found signals of divergent selection with increased genetic differentiation close to QTLs. Extensive interactions between QTLs and traits suggested a QTL architecture that is resistant to hybridization. Abstract: Knowledge of the genetic basis of phenotypic divergence between species and how such divergence is caused and maintained is crucial to an understanding of speciation and the generation of biodiversity. The hybrid zone between Senecio aethnensis and S. chrysanthemifolius on Mount Etna, Sicily, provides a well-studied example of species divergence in response to conditions at different elevations, despite hybridization and gene flow. Here, we investigate the genetic architecture of divergence between these two species using a combination of quantitative trait locus (QTL) mapping and genetic differentiation measures based on genetic marker analysis. A QTL architecture characterized by physical QTL clustering, epistatic interactions between QTLs, and pleiotropy was identified, and is consistent with the presence of divergent QTL complexes resistant to gene flow. A role for divergent selection between species was indicated by significant negative associations between levels of interspecific genetic differentiation at mapped marker gene loci and map distance from QTLs and hybrid incompatibility loci. Within-species selection contributing to interspecific differentiation was evidenced by negative associations between interspecific genetic differentiation and genetic diversity within species. These results show that the two Senecio species, while subject to gene flow, maintain divergent genomic regions consistent with local selection within species and selection against hybrids between species which, in turn, contribute to the maintenance of their distinct phenotypic differences.